TABARI AND HIS COMMENTARY ON CORAN - M. F. Murtazin (Гуманитарные и юридические исследования)
The article is devoted to the biography of a famous Moslem Arab historian and theologian Tabari. The author explores main stages of the development of his scientific and religious activities, as well as a summary of his commentary on Coran.